Factors contributing to the retention of natural mentors among underrepresented students across the first year of college. Issue 1 (1st January 2018) - Negrete, Andrea; Griffith, Aisha N.; Hurd, Noelle M.
Abstract: The current study examined characteristics of natural mentoring relationships (NMRs; i.e. mentoring relationships that develop organically with adults in one's pre-existing social network) among underrepresented college students as contributors to NMR retention across the first year of college. The sample consisted of 209 underrepresented college students (73% female; mean age = 18.1, SD = .35) who reported having a natural mentor during the first semester of college. Each participant could report up to five natural mentors and a total of 550 NMRs were reported. We found that more frequent contact and greater relational closeness with natural mentors during the Fall semester of mentees' first year of college increased the likelihood that NMRs were retained through the Spring semester of the first year. These findings shed light on aspects of NMRs that may be most central to fostering their duration during difficult transitional spaces.